2021
DOI: 10.1111/jopr.13401
|View full text |Cite
|
Sign up to set email alerts
|

Digital Workflow for Establishing the Posterior Palatal Seal on a Digital Complete Denture

Abstract: The posterior palatal seal (PPS) plays important roles in improving denture retention, preventing food and debris from entering under the denture base, reducing the gag reflex, providing more strength across the denture, and making the distal border less noticeable to the tongue. Digital dentures have become popular, owing to the use of computer‐aided design and computer‐aided manufacturing and rapid prototyping technologies. However, limited research has been conducted on a digital workflow to establish the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…PPS subgroups in the maxillary arches were selected because they are essential in achieving intimate contact with maxillary complete dentures. 40 As mentioned previously, the superimposition of the two scan datasets yields a single outcome. This indicates that the scan datasets' relative positions are only meaningful and have constant values.…”
Section: Discussionmentioning
confidence: 87%
“…PPS subgroups in the maxillary arches were selected because they are essential in achieving intimate contact with maxillary complete dentures. 40 As mentioned previously, the superimposition of the two scan datasets yields a single outcome. This indicates that the scan datasets' relative positions are only meaningful and have constant values.…”
Section: Discussionmentioning
confidence: 87%
“…The designing approach follows accurate bead line dimensions and can be considered a novel application of digital technology. The open architecture of intraoral digital scanning combined with CAD‐CAM systems can aid in modifying the STL file to perform digital sculpting of the posterior palatal seal for CAD‐CAM complete dentures 11 or for creating digital bead lines for maxillary reduced palatal coverage implant‐supported overdenture in this presented digital technique and concept.…”
Section: Discussionmentioning
confidence: 99%
“…29,30,[36][37][38][39][40] Therefore, for fabricating complete dentures or Kennedy Class I and II removable partial dentures, digitizing conventional impressions by using IOSs have been recommended. 29,30,[36][37][38][39][40] Similarly, complete-arch scans by using IOSs for fabricating complete-arch tooth-and implant-supported rehabilitations have shown contradictory results in the literature regarding reliability and accuracy. [31][32][33][34][35]41,42 Different techniques have been described to improve the scanning accuracy of complete-arch implant digital scans; however, due to the limited clinical data published, a systematic recommendation of complete-arch implant digital scans by using IOSs is difficult.…”
Section: Ios Technology and Systemmentioning
confidence: 99%
“…30 Published studies have shown that intraoral digital scans can accurately digitized edentulous areas with firm attached tissue and mucosa, but capturing areas with mobile tissue by using an IOS is challenging, regardless of the scanning technology and system elected. 29,30,[36][37][38][39][40] Therefore, for fabricating complete dentures or Kennedy Class I and II removable partial dentures, digitizing conventional impressions by using IOSs have been recommended. 29,30,[36][37][38][39][40] Similarly, complete-arch scans by using IOSs for fabricating complete-arch tooth-and implant-supported rehabilitations have shown contradictory results in the literature regarding reliability and accuracy.…”
Section: Ios Technology and Systemmentioning
confidence: 99%
See 1 more Smart Citation